COMPARATIVE ANALYSIS OF ECOTOURISM STATISTICS ACROSS COUNTRIES - Toshpulatova Mokhinur (Journals Park Publishing, 2025)
Ecotourism has emerged as a significant aspect of sustainable tourism, attracting attention worldwide for its potential to promote environmental conservation and socio-economic development. This study conducts a comparative analysis of ecotourism statistics across ten countries to examine trends, variations, and factors influencing ecotourism performance. Statistical comparisons include visitor numbers, revenue generated, and ecological impacts, providing insights into the state of ecotourism globally.
Keywords: Ecotourism, policy frameworks, natural attractions, ecotourism’s positive effects, national tourism boards, analyze statistics, partnerships.